Adventures with atoms and molecules. Book V : chemistry experiments for young people - Mebane, Robert C.; Rybolt, Thomas R. (Springfield, NJ : Enslow, 1995)
Chemistry experiments for home or school demonstrate the properties and behavior of various kinds of atoms and molecules.
Includes index.
Wilson's Junior High School.
6.5.
6.5
5-8
Keywords: Chemistry -- Experiments -- Juvenile literature; Chemistry -- Experiments; Experiments; Molecules -- Experiments; Chemistry -- Experiments; Molecules -- Experiments; Science -- Experiments